The novel habits of happiness - McCall Smith, Alexander, 1948- (McCall Smith, Alexander, 1948- Isabel Dalhousie series., 2015)
"The ever-delightful, insatiably curious Edinburgh philosopher and amateur sleuth returns to take on a case unlike any she's had before--this one with paranormal implications--in the tenth installment of this beloved author's consistently best-selling series. From a small town outside Edinburgh comes the news that a young boy has been recounting vivid recollections of a past life: a perfect description of an island off the coast of Scotland which he couldn't possibly know, and a house there, where he claims to have spent his former life. When the boy's mother asks Isabel to investigate his claims, she feels she must--of course!--help them learn the truth, and she and her husband, Jamie, set off for the island. But finding the house the boy described only leads to more complicated questions. And when she learns about the unusual story of the family who lived there, Isabel is suddenly faced with a situation of extraordinary delicacy that will require all of her skills both as sleuth and philosopher"--